2004
DOI: 10.1108/14714170410815114
|View full text |Cite
|
Sign up to set email alerts
|

Construction safety management: an exploratory study from China

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 27 publications
0
25
0
2
Order By: Relevance
“…Appropriate special construction plans are essential technical documents used to guide management and operations. Safety inspection [28,30,31,35,37,[40][41][42][43][44][45] Safety programs may require safety managers (e.g., safety supervisor, project manager, and safety officer, etc.) to conduct adequate inspection during construction to protect workers from workplace hazards.…”
Section: Numbermentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate special construction plans are essential technical documents used to guide management and operations. Safety inspection [28,30,31,35,37,[40][41][42][43][44][45] Safety programs may require safety managers (e.g., safety supervisor, project manager, and safety officer, etc.) to conduct adequate inspection during construction to protect workers from workplace hazards.…”
Section: Numbermentioning
confidence: 99%
“…Detailed safety management plans and safety goals should be discussed and determined through such meetings. Management support [10,11,40,45,48,51,[54][55][56][57] Management support can ensure that sufficient resources are allocated for safety management, and proper actions are conducted to improve safety performance.…”
Section: Numbermentioning
confidence: 99%
“…b) Safety training is traditionally based on indoor teaching, which lacks interaction, intuition and hands-on training, and therefore marginally improves the safety consciousness of workers [9]. c) Safety officers often apply inappropriate site monitoring as they simply use a checklist to manage construction safety by identifying and recording violations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, unsafe behavior may arise due to a worker's state of mind, tiredness, stress, or physical condition (Schaufelberger and Lin, 2014). Also, many factors such as insufficient and poor communication, sub-contracting to negligent firms, lack of H&S training and low educational level of construction staff members leads to accidents as affirmed by Cheng et al (2004). Schaufelberger and Lin (2014) recognized some examples of accident causes, such as:…”
Section: Causes Of Construction Accidentsmentioning
confidence: 99%
“…The HSE in the United Kingdom declared that approximately 80% of accidents are attributable to human behavior (cited by Li and Poon, 2013). Cheng et al (2004) stated that low educational level of construction staff members is a factor that leads to accidents such as lack of training, insufficient and poor communication error and sub-contracting to negligent firms. Thorpe (2005) and Twort and Rees (2011) suggested that employers should prepare employees before starting construction work and provide relevant information to identify H&S risks to avert risks to their H&S. Moreover, awareness on the part of contractors is essential to encourage workers to follow H&S instructions.…”
Section: Accidents and Injuriesmentioning
confidence: 99%